2013
DOI: 10.1164/rccm.201301-0132oc
|View full text |Cite
|
Sign up to set email alerts
|

The Endothelin A Receptor Mediates Fibrocyte Differentiation in Chronic Obstructive Asthma. The Involvement of Connective Tissue Growth Factor

Abstract: Our findings demonstrate for the first time that the ETAR pathway is vital for CTGF expression, which results in fibrocyte differentiation in COA, and suggests that an ETAR antagonist may be a potential antifibrotic agent in preventing the development of fibrosis in patients with COA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 45 publications
1
50
0
Order By: Relevance
“…CTGF, a fibrotic factor, has been reported to be upregulated in other inflammatory diseases such as COPD and asthma, promoting increased fibrogenesis and remodeling of the airway tract. 29,30 Earlier studies have shown that rapamycin increased CTGF expression via TGF-b signaling pathway in lung epithelial cells and lung fibroblasts. 28,35 These studies also support our finding that CTGF may play a role in CF lung fibrosis through elevated miR-155 expression and consequent suppression of RPTOR levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTGF, a fibrotic factor, has been reported to be upregulated in other inflammatory diseases such as COPD and asthma, promoting increased fibrogenesis and remodeling of the airway tract. 29,30 Earlier studies have shown that rapamycin increased CTGF expression via TGF-b signaling pathway in lung epithelial cells and lung fibroblasts. 28,35 These studies also support our finding that CTGF may play a role in CF lung fibrosis through elevated miR-155 expression and consequent suppression of RPTOR levels.…”
Section: Discussionmentioning
confidence: 99%
“…28 CTGF is induced by physical, chemical or biological external stimuli (such as mechanical stretch, hypoxia or inflammation), and activates fibroblasts for more collagen synthesis, which leads to fibrosis. 17,18 Even though CTGF expression is high in several respiratory diseases such as asthma and emphysema, 29,30 its role in CF has not been examined. Interestingly, we found that IB3-1 CF cells exhibited increased expression of CTGF compared to IB3-1/S9 control cells (Figs.…”
Section: Ctgf Is Induced In Cf Lung Epithelial Cellsmentioning
confidence: 99%
“…[1][2][3][4] Fibrocytes are increased in peripheral blood 5,6 and the airway wall, 7 particularly in airway smooth muscle bundles of asthmatic patients. 8 The positive correlation between the number of a-smooth muscle actin-positive fibrocytes and the thickness of the lamina reticularis supports the notion that fibrocyte-derived myofibroblasts might contribute to the deposition of the subepithelial extracellular matrix.…”
mentioning
confidence: 99%
“…Furthermore, the effects of persistent asthma on fixed airway obstruction were synergistic with smoking, but only in those with atopy. The other studies focused on potential mechanisms of airway remodeling including fibrocytes and their products, connective tissue growth factor, and endothelin-1 (58), and markers of vascular perturbation in asthma, von Willebrand factor propeptide and P-selectin (60). In an interesting study of tissue remodeling in a condition closely related to asthma, Takabayashi and colleagues studied fibrin deposition in chronic rhinosinusitis (61).…”
Section: Pathways That Affect Airway Remodeling and Cause Fixed Airflmentioning
confidence: 99%